2006
DOI: 10.1097/01.brs.0000227288.00378.d5
|View full text |Cite
|
Sign up to set email alerts
|

Work Retention and Nonspecific Low Back Pain

Abstract: Psychosocial and physical factors are associated with work retention for patients with nonspecific LBP. The predictive value of certain constructs may vary with the time when they are assessed and how outcome is operationalized. Further studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In 2 studies, investigators reported that the depression 15 and somatization subscores 6 were associated with work status. These conclusions differ from ours, in which we did not find an association between either of these subscores and work status.…”
Section: Association Between Depression and Somatization And Pain Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2 studies, investigators reported that the depression 15 and somatization subscores 6 were associated with work status. These conclusions differ from ours, in which we did not find an association between either of these subscores and work status.…”
Section: Association Between Depression and Somatization And Pain Andmentioning
confidence: 99%
“…Different conclusions among studies can be attributable to different samples and study designs. In 2 of the studies, 6,15 the investigators limited their sample to individuals participating in a work rehabilitation program. None of these studies evaluated for the effect of receiving physical therapy for the management of low back pain.…”
Section: Association Between Depression and Somatization And Pain Andmentioning
confidence: 99%
See 1 more Smart Citation
“…3,19,65 PD has been identified as an important prognostic variable to identify patients with lumbar impairment who are at high risk for developing or sustaining chronic disability. 4,11,12,35,40,41,43 Failure to identify patients with lumbar impairment who experience elevated PD may be problematic, because evidence demonstrates an important association between elevated PD and poor treatment outcomes, increased healthcare utilization, and T T STUDY DESIGN: Prospective, longitudinal, observational cohort design.…”
mentioning
confidence: 99%
“…Psychological complications are an inseparable part of industrial life..[1–3] Screening of these complications is important as far as social health is concerned. Part of these complications are due to physical factors existing in different occupational activities.…”
Section: Introductionmentioning
confidence: 99%